Perlakuan Akuntansi Aset Biologis Berdasarkan Psak 69 Pada Peternakan Burung Puyuh PT Madania Kabupaten Magelang - Akmala, Vaza; wibowo, heri (Politeknik Sawunggalih Aji, 2025)
PT Madania is a company engaged in the livestock sector. This farm has biological assets in the form of quails that produce quail eggs as the main product for sale. This study aims to determine the accounting treatment of biological assets in the form of quails and how they are in accordance with the Financial Accounting Standards Statement (PSAK) 69 concerning Agriculture. The data in the study are in the form of primary data obtained through direct interviews with farm owners regarding the quail farming cycle starting from feeding, giving vitamins, cleaning the cage, the process of producing eggs, to culling quails, direct observation at the PT Madania quail farm in Magelang Regency and literature study at the Sawunggalih Aji Purworejo Polytechnic library. The analysis technique used is descriptive analysis by describing data according to the research problem, and arranged systematically based on PSAK 69. The method used is a census sampling approach with the entire population used as a research sample. The results of the study indicate that the owner of the PT Madania farm has not implemented PSAK 69 in recording its biological assets. This situation causes the company to be unable to calculate profits accurately, thus creating risks in financial decision making. Keywords: accounting, biological assets, PSAK 69.